Peranan Pemerintah Daerah di Era Reformasi - Mhd Ansori (Wajah Hukum, 2018)
The republic of Indonesia as a unitary state embraces the principle of decentralization in the administration of goverment, by providing opportunies and freedom to the region to organize regional autonomy. Thus, regional autonomy is a policy that is in accordance with the principle of decentralization within the framework of the unitary state of the Indonesian republic. The real autonomy is the flexibility of the region to exercise the authority of the goverment in certain areas that are real and necessary and growing, living and developing in the regions. Of course this is to realize independence, autonomy is closely related to the pattern of relation between the central and regional which includes various aspects of the relationship of authority, supervisory relations, financial relations, and so forth traditional. Soewargono and Djohan stated that one of the main functions of goverment is to make public policy. The role of goverment is more as a servant of society that does not aim to gain profit rather than fulfill what the bureaucracy’s own will. The purpose of this paper to know the role of local goverment in the current era of reformasi. The type of research used is normative juridical research, using conceptual approach, legislation approach, and historical approach.